Late Cenozoic of Península Valdés, Patagonia, Argentina : an interdisciplinary approach - Bouza, Pablo; Bilmes, Andrés (Springer, 2017)
This book presents extensive and new information on the Cenozoic marine and continental systems of one of the most important world heritage sites of Southern South America: The Península Valdés. From an interdisciplinary approach, that includes geological, biological and archeological perspectives of more than 30 specialists, an integrated description and analysis of the Cenozoic environments of the study region is carried on. The volume brings together an update of the geology, climate, geomorphology, soils, biodiversity, archeology and human impact of the Península Valdés. The scope of this book extends to any natural science researcher of the world interested on the Cenozoic history of the Península Valdés.
Keywords: Geology -- Argentina -- Valdés Peninsula.; Geology, Stratigraphic -- Cenozoic.; Argentina -- Valdés Peninsula.; From 65 million years ago; elektronické knihy; electronic books